Risk taking in the market of speculative exchange-traded retail products: Do socio-economic factors matter? - Stefanie Baller (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2017)
When purchasing a financial product, investors may actively decide upon the risk they take. This paper analyzes the impact of investors' personal characteristics, location-based demographic factors and transaction-specific trading surroundings on their risk taking in the market of speculative exchange-traded retail products. Using a large trade dataset of warrants and leverage certificates on an individual investor level, I find evidence that risk taking behavior is strongly determined by the characteristics examined here: (i) Inexperienced young males with little secure status in their lives take more risk than other traders. (ii) Living in socially less desirable environments or encountering less risky trading conditions also supports risk taking. (iii) Risk taking is highly persistent. (iv) Finally, higher risk taking leads to poorer performance.
Keywords: D40; G11; G21; G24; Z10; 650; Leverage Certificate; Warrant; Private Investor; Risk Taking; Performance; Socio-Economic Factors